Fluorescence Reduction Neutralization Test: A Novel, Rapid, and Efficient Method for Characterizing the Neutralizing Activity of Antibodies Against Dengue Virus - Jiazheng Guo; Jiansheng Lu; Peng Du; Kexuan Cheng; Chao Lei; Yujia Jiang; Meiling Peng; Yating Li; Kaiyue Sun; Changyan Xu; Yunzhou Yu; Chen Gao; et al. (Current Issues in Molecular Biology)
Dengue virus (DENV) is a major public health threat in the tropical and subtropical regions of the world. Climate change resulting from global warming is further expanding DENV–endemic areas, adversely affecting public life and health. Despite this, no specific drug against DENV has been developed so far. Vaccines and neutralizing antibodies are the chief preventive and therapeutic tools for managing pathogenic infections. The present study describes the development of a novel fluorescence reduction neutralization test (FRNT) for evaluating the neutralizing activity of antibodies against DENV. This FRNT allows rapid antibody screening. In addition, we calculated the FRNT50 to indicate the neutralizing ability of the antibodies. In contrast to the conventional plaque reduction neutralization assay, the FRNT has a shorter experimental cycle, a simpler operation, and greater objectivity, which can greatly accelerate the research and development process of vaccines and antibodies against DENV.